Peran Burnout sebagai Pemediasi Pengaruh Workload terhadap Turnover Intention pada Pekerja Gen Z di Kota Malang - Lestari, Alisca Umi; Almanshur, Fauzan; Ekowati, Vivin Maharani (Jurnal Manajemen Bisnis dan Keuangan, 2025)
Human resources are a very important asset for companies. Therefore, companies need to ensure that the employee turnover rate remains low. The purpose of this study is to test the role of burnout as a mediator of the effect of workload on turnover intention among Generation Z workers in Malang City. This study employs a quantitative approach with a population consisting of all Generation Z workers employed in Malang City. The study sample comprised 100 respondents determined using the Lemeshow formula and analyzed with the Partial Least Squares (PLS) technique. The results indicate that workload has no significant effect on turnover intention, workload has a significant effect on burnout, and burnout mediates the relationship between workload and turnover intention.